The Implementation of Teams Game Tournament (TGT) to Improve Students’ Writing Ability of Second Grade Students in Junior High School Level - Ananda, Feby; Rahma, Dania; Suparmi (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
This pre-experimental study examined the effectiveness of the Teams Game Tournament (TGT) in enhancing the writing abilities of second-grade English learners at 7th State Junior High School in Padang. The research involved 33 students from class VIII.5, employing a one-group pre-test/post-test design to measure the impact of TGT implementation. Quantitative data analysis revealed a substantial increase in students' writing scores following the intervention. Specifically, the post-test average score (89.45) significantly surpassed the pre-test average (60.24). A t-test analysis yielded a t-value of 11.54, which exceeded the t-table value of 1.697 at a 0.05 significance level, with 32 degrees of freedom. This statistically significant difference confirmed the study's hypothesis, indicating that TGT effectively improved students' English writing skills. The findings suggest that TGT is a valuable pedagogical strategy for enhancing writing proficiency in English language learning.